(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Article 370 of the Indian Constitution specifies self-rule for the province of Jammu and Kashmir (JK). Terms of the Article have stayed buried in discussion attributable to its inconsistent allotment inside the system of free India. This paper analyzes Article 370 and the legitimacy of politics joined to it, in light of four explicit contentions. In the first place, the Genesis of Article 370 brings forth disparity in India. Second, its Retention suggests the putrefying of petulant issues. Third, its Ramifications produce imbalance inside JK. Fourth, how Politics over Article 370 just look for constrained influence from it. These contentions have been inspected through commitment with essential and optional sources and perspectives broken down in various conventions. An interpretive methodology orders this discussion in the bigger setting of Continuation or Revocation of Article 370 and in light of the examining the question whether Article 370 has worked in the way imagined, or has disturbed imbalance and fuelled the development of contention in JK.